2016
DOI: 10.18632/oncotarget.13712
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immune responses toward tumor-derived antigens in previously untreated patients with chronic lymphocytic leukemia

Abstract: In chronic lymphocytic leukemia (CLL) the occurrence and the impact of antibody responses toward tumor-derived antigens are largely unexplored. Our serological proteomic data show that antibodies toward 47 identified antigens are detectable in 29 out of 35 patients (83%) with untreated CLL. The glycolytic enzyme alpha-enolase (ENO1) is the most frequently recognized antigen (i.e. 54% of CLL sera). We show that ENO1 is upregulated in the proliferating B-cell fraction of CLL lymph nodes. In CLL cells of the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…In addition, we previously reported that polyclonal antibodies directed to recurrent antigens expressed by tumor cells can be frequently found in the serum of CLL patients, especially those with progressive disease. However, these antibodies are inefficient in triggering ADCC and complement-derived cytotoxicity (CDC) (153). Alterations in the classical components of the complement cascade are reported in almost 40% of CLL patients, and contribute to the compromised CDC and to their increased susceptibility to infections (154,155).…”
Section: Humoral Immune Responsementioning
confidence: 99%
“…In addition, we previously reported that polyclonal antibodies directed to recurrent antigens expressed by tumor cells can be frequently found in the serum of CLL patients, especially those with progressive disease. However, these antibodies are inefficient in triggering ADCC and complement-derived cytotoxicity (CDC) (153). Alterations in the classical components of the complement cascade are reported in almost 40% of CLL patients, and contribute to the compromised CDC and to their increased susceptibility to infections (154,155).…”
Section: Humoral Immune Responsementioning
confidence: 99%
“…Decreased invasion in vitro and metastasis in vivo [71] are decreased in stage IV lung and breast cancers [88] , and are lower in stage III/IV than in stage I/II lung cancer patients [89] . By contrast, the presence of anti-a-enolase antibodies in sera from chronic lymphocytic leukaemia (CLL) patients is predictive of a shorter time to first treatment [90] , indicating that the presence of a-enolase antibodies are indicative of a disrupted immune system in CLL. Taken together, these studies suggest that autoantibodies against a-enolase are a good prognostic factor in pancreatic, lung and breast cancers, and provide further evidence that targeting a-enolase may be beneficial in solid tumours.…”
Section: Knockdown In Hec-1b and Ishikawamentioning
confidence: 99%
“…Polyamine sulphonamide analogues have proven particularly effective at inhibiting a-enolase activity. Two such compounds have been further developed and shown to Chordoma Cervical or sacral spine chordomas (n = 39) Increased protein expression was associated with worse disease-free survival [83] CLL Sera from CLL patients (n = 86) Presence of anti-a-enolase antibodies was predictive of a shorter time to first treatment [90] Colorectal cancer Colorectal tumour tissues (n = 41) Protein expression correlated with tumour size and distant metastasis [11] Endometrial cancer Endometrial cancer tissue (n = 100) Protein expression correlated with lymph node status and depth of myometrial invasion; patients with high expression had worse OS [12] Gastric cancer Gastric cancer tissue (n = 76) Protein expression correlated with lymph node metastasis and TNM stage [60] TCGA dataset (n = 410 gastric cancer patients); Gastric cancer tissue (n = 94)…”
Section: Enolase Inhibitors Are Potential Anticancer Agentsmentioning
confidence: 99%
“…Reasons for this higher risk are multifactorial ( Table 1). First, hematologic malignancies are directly tied to an immunocompromised status due to humoral and cellular immune dysfunction (17)(18)(19)(20). Second, a large number of therapies employed for hematologic malignancies are highly immunosuppressive, even more than standard chemotherapies used for solid tumors.…”
Section: Risk Factors For Covid-19 In Patients With Hematologic Maligmentioning
confidence: 99%